THE ANALYSIS OF PECULIARITIES OF PERSONAL ANXIETY EXPERIENCED BY PROFESSIONALS OF SOCIOEDUCATIONAL ACTIVITIES OF LITHUANIA - Alifanovienė, Daiva; Vaitkevičienė, Asta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article analyses the peculiarities of the anxiety state of professionals of socioeducational activities (social pedagogues and social workers). Employing Spielberger’s and Chanin’s personal anxiety scale, the level of personal anxiety was identified, and, using a semi-structured interview, situations provoking anxiety experienced by professionals of socioeducational activities were identified. Data of anxiety experienced by social pedagogues and social workers in 2011 were analysed employing the factor analysis method of multi-dimensional statistics, the data of the semi-structured interview were processed using the content analysis method. It was identified that about half of the respondents experienced a moderate level of personal anxiety, enabling to mobilise, look for innovative solutions in professional activities. Severe level of personal anxiety was identified for slightly less than half of respondents; it was perceived as dangerous and preventing professionals of socioeducational activities from successful development of professional activities and even warning about possible psychosomatic disorders.